DON RIGOBERTO’S SEXUAL FANTASY IN MARIO VARGAS LLOSA IN PRAISE OF THE STEPMOTHER (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2014)
DON RIGOBERTO’S SEXUAL FANTASY IN MARIO VARGAS LLOSA IN PRAISE OF THE STEPMOTHER Dinda Anisa Larasati English Department, Language and Arts Faculty, State University of Surabaya dinda_kdy@yahoo.com Drs. Much. Khoiri M.Si. English Department, Language and Arts Faculty, State University of Surabaya much_choiri@yahoo.com Abstract Sexuality is seen as sinful thing which influences Christian to behave and act based on the society role. Some people tend to repress their sexual fantasy because sexual fantasy is a genre that can lend itself very easily to the sexual elements of life, the depraved, the debauched, or the downright saucy and controversial. The aim of this study is to describe how Don Rigoberto’s sexual fantasy depicted in Mario Vargas Llosa In Praise of the Stepmotherand and to reveal how Don Rigoberto’s sexual fantasy can impact on his wife. The data are in the form of quotation, fragments, and dialogues or monologues that indicated the thoughts and action concerning form of sexual fantasy.The data is applying the theory of fantasy by Jacques Lacan and supported with Baron. This study also uses the concept of anxiety and psychological trauma. Initially, Don Rigoberto obsessed with three things: Physical Hygiene, sex with his wife, and erotic paintings. He devotes a day a week for the care of a different member or organ.His love life with Lucrecia in a world more imaginary than real, of what he wishes she were than what she really is. He always lost in his dream which is imagined erotically things from some media and those can support his sexual fantasy. Don Rigoberto forced his wife (to have) sex with another man which can be deeply shocking for her. Those facts are proof that Don Rigoberto get his satisfaction from his obsession. Keywords: sexuality, fantasy, desire, anxiety, psychological trauma Abstrak Seksualitas dipandang sebagai hal yang berdosa yang mempengaruhi Kristen untuk bersikapdanbertindak berdasarkan peran masyarakat. Beberapa orang cenderung untuk menekan fantasi seksual mereka karena fantasi seksual adalah genre yang dapat menjatuhkan diri seseorang ke dalam unsur-unsurseksualkehidupan, buruk, yang tidak bermoral, dan kontroversial. Tujuan dari skripsi ini adalah untuk menggambarkan bagaimana fantasi seksual Don Rigoberto yang digambarkan di Mario Vargas Llosa In Praise of the Stepmother dan mengungkapkan bagaimana fantasi seksual Don Rigoberto yang berdampak pada istrinya. Di dalam data tersebut terdapat kutipan, fragmen, dan dialog atau monolog yang menunjukkan pemikiran dan tindakan mengenai bentukfantasi. Untuk data seksual menerapkan teori fantasi dari Jacques Lacan dan didukung dengan Baron. Analisis ini juga menggunakan konsep anxiety dan psychological trauma. Pada awalnya, Don Rigoberto terobsesi dengan tiga hal: Fisik higienis, seks dengan istrinya, dan lukisan erotis. Dia menjadikan satu hari dalam seminggu untuk melakukan perawatan pada anggota atau organ badan yang berbeda. Kehidupan cintanya dengan Lucrecia di dunia lebih kepada imajinasi daripada kenyataan, apa yang dia ingin adalah berada dari apa yang sebenarnya dia. Dia selalu terjebak dalam mimpinya, yaitu dengan membayangkan hal-hal erotis dari beberapa media dan mereka dapat mendukung fantasi seksualnya. Don Rigoberto memaksa istrinya untuk berhubungan seks dengan laki-laki lain dan hal itu sangat mengejutkan istrinya.Faktanya adalah bukti bahwa Don Rigoberto mendapatkan kepuasan melalui obsesinya. Kata kunci: sexuality, fantasy, desire, anxiety, psychological trauma Introduction Human cannot be separated with needs. There are three basic drives such as eating, sleeping, and sex. As a normal human being, sexuality is given from the beginning ourselves. Nietzche asserts that “we are not only rational out being, but we are also full of desire, with the drives and hidden longing, which formed, our ideas and views about the world” (O’Donnel, 2008: 41).In reality, sexuality describes a huge range of activities. This is half of dialectic, anything can be sex because sex has whatever meaning human experience moment by moment, and sex hasan infinite range of meanings because the scope of activities that can properly be called sexual is so vast. Lisa Downing says that sexuality is something that we ourselves create-it is our own creation, and much more than the discovery of secret side of our desire. Sex is not fatally, it is possible to creative life (Downing 2008:104). Sex can make people different. It means that sex is created because of love, relationship, and perhaps necesity or situation. Sex is not taboo anymore in this modern era, but sex can help viability in science. In psychoanalyticterms, sexuality plays an enormously influential rolein psychological development.From a veryearly age, how people experience their bodies in relation to the physical world as well as to the internal stimuli and feelings their bodies generate profoundly effects how they view the world and themselves.In particular,conscious and unconscious fantasies are about human’s bodies and sexuality influence the development of stable patterns of sexual identity, and with that,sexual behaviors.(http://psychoanalysis101.org/psycho-sexual-development/). Sexual fantasies play a central role in mental life, despite – or rather: because of – the fact that they in particular meet the fate of repression, which is why Freud calls them “the weak spot in our psychical organization” (Freud, 1911: 223). This repression creates the psychic disposition towards neurosis in man, the conflict between unconscious desires and conscious control. That sexuality is actually the weak spot in man’s psychical organization is proven by the fact that many (predominantly male) users of the Internet cannot resist the temptation to seek sexual pleasure via the computer screen. Sex is still the biggest business on the net, offering such a massive electronic hallucination of gratifying objects. In Praise of the Stepmother with Mario Vargas Llosa as the author, Mario Vargas Llosa, which reached worldwide recognition with his novels Pantoja and the Special Aunt Julia and the Scriptwriter, The War of the Worlds.In Praise of the Stepmother, made a foray into a genre that is emerging in many of his works, the erotic. Sex in the novels may offend, amuse, or worse. As this study has come toexpect of VargasLlosa as the author of this novel, he uses a precisely structured form to present the distinct components of his story. Structure can be invaded or skewed which is an interesting way to make point innocence and morality are strong themes which are compound in unusual ways. In Praise of the Stepmother with Mario Vargas Llosa as the author, Mario Vargas Llosa, which reached worldwide recognition with his novels Pantoja and the Special Aunt Julia and the Scriptwriter, The War of the Worlds.In Praise of the Stepmother, made a foray into a genre that is emerging in many of his works, the erotic. Sex in the novels may offend, amuse, or worse. As this study has come toexpect of VargasLlosa as the author of this novel, he uses a precisely structured form to present the distinct components of his story. Structure can be invaded or skewed which is an interesting way to make point innocence and morality are strong themes which are compound in unusual ways. Mario Vargas Llosa was born in Arequipa, the second city of Peru, in March 1936.In 1958 he travelled to Paristhanks to a prize won in a short story competition,and on his return to Lima he completed his higher education and received a grant to transfer to theUniversity of Madrid. A few months after arriving in the capital of Spain,he left his studies for the doctorate and settled in Paris, where he was to stay for seven years.In 1963 he published his first great novel,